Long-term Results of Optical Laser Urethrotomy for Post-traumatic Stricture of the Membranous Urethra - Nurberdiev, Aluadin; Suchshenko, Alexey; Muralovich Kazhitaev, Almas; Zhanbyrbekuly, Ulanbek; Khairli, Gafur (West Kazakhstan Medical Journal, 2024)
Urethral stricture is a common condition characterized by the narrowing of the urethra, leading to difficulty in urination. This article presents a case report of a 47-yearold male with urethral stricture following a pelvic fracture. The patient presented with urinary retention and a history of traumatic injury. Diagnostic imaging revealed a 2.0-2.2 cm stricture in the membranous urethra. Surgical intervention, including optical laser urethrotomy and silicone urethral catheter placement, was performed successfully. Postoperative management included antibacterial and anti-inflammatory therapy, leading to the restoration of independent urination. Urodynamic examination confirmed the successful outcome of the surgery. This case demonstrates that endoscopic surgery for urethral strictures can have a favorable prognosis. However, due to the potential for recurrence, ongoing outpatient care and monitoring by a urologist are essential for these patients.